2018
DOI: 10.1002/jmr.2759
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity and immune system dysregulation in schizophrenia: IgGs from sera of patients hydrolyze myelin basic protein

Abstract: Several different theories of schizophrenia (SCZ) were discussed; the causes of this disease are not yet clear. Using ELISA, it was shown that titers of autoantibodies against myelin basic protein (MBP) in SCZ patients are ~1.8-fold higher than in healthy individuals but 5.0-fold lower than in patients with multiple sclerosis. Several rigid criteria were checked to show that the MBP-hydrolyzing activity is an intrinsic property of SCZ IgGs. Approximately 82% electrophoretically homogeneous SCZ IgGs purified us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 59 publications
(244 reference statements)
3
42
0
2
Order By: Relevance
“…Therefore, catalytic cross-reactive antibodies against histones and MBP can play a negative role, contributing to the development of the disease [ 47 ]. Recently, we detected catalytic antibodies in serum of patients with schizophrenia that hydrolyze MBP [ 48 ]. Therefore, it was interesting to establish whether histone-hydrolyzing antibodies are formed in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, catalytic cross-reactive antibodies against histones and MBP can play a negative role, contributing to the development of the disease [ 47 ]. Recently, we detected catalytic antibodies in serum of patients with schizophrenia that hydrolyze MBP [ 48 ]. Therefore, it was interesting to establish whether histone-hydrolyzing antibodies are formed in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DNA-and MBP-hydrolyzing abzymes were found in SLE and MS patients [24,25]. Moreover, abzymes hydrolyzing DNA and MBP was revealed in sera of patients with schizophrenia also demonstrating neuropsychiatric components [44,45]. Thus, changes in the HSCs differentiation profiles and the intensity of production of abzymes with various activities in patients with different AIDs and experimental animals prone to the development of autoimmune reactions may vary in one way or another.…”
Section: Discussionmentioning
confidence: 98%
“…The K m and V max values were estimated using the nonlinear regression method in the Origin Pro v.8.6 program and were presented as linear transformations using a Lineweaver-Burk plot [54]. The value of K cat was determined by the formula K cat = V max /½AB, where [AB] is the total concentration of IgGs in the reaction mixture [40,42,49]. Errors in the values were within 7-15%.…”
Section: Silver Staining Methodmentioning
confidence: 99%
“…The stability of any abzymes to these conditions is relatively low, so their activity is significantly reduced immediately after gel filtration. It has been previously shown that activity of IgGs was restored after their neutral solutions were kept at 40°C for 1-2 weeks [40,42].…”
mentioning
confidence: 99%